Physical activity, fatigue severity, and health-related quality of life of community-dwelling stroke survivors: a cross-sectional study - Marufat Oluyemisi Odetunde; Ayomide Felix Makinde; Olamide Mary Jimoh; Chidozie Emmanuel Mbada; Faatihah Niyi-Odumosu; Francis Fatoye (Bulletin of Faculty of Physical Therapy, 2025)
Abstract Background Physical inactivity among stroke survivors (SSV) may result from fatigue, physical disabilities, and psychosocial factors, all of which adversely affect health-related quality of life (HRQL). Studies on combined interactions among physical activity (PA), fatigue severity (FS), and HRQL in SSV are scarce. This study was aimed to determine the relationships among PA, FS, and HRQL in community-dwelling SSV and to predict the association with selected socio-demographic and clinical variables. Methods This analytical cross-sectional correlation study involved 102 consented community-dwelling SSV. Respondents were purposively recruited from physiotherapy outpatient clinics of selected secondary and tertiary hospitals in southwest Nigeria. PA, FS, and HRQL of the SSV were assessed using the Stroke Physical Activities Questionnaire (SPAQ), Fatigue Severity Scale (FSS), and Stroke-Specific Quality-of-Life (SS-QoL) scale, respectively. Information on respondents’ socio-demographic and clinical characteristics was also collected. Data were analyzed using descriptive and inferential statistics at p < 0.05 significance level. Results Respondents’ mean age was 59.98 ± 11.59 years. The majority were females (52.9%), had ischemic stroke (72%), and with right-side weakness (54%) of over 6 months (80%). Respondents’ mean scores on SPAQ, FSS, and SS-QoL scales are 1867.47 ± 1817.93 MET min/week, 31.94 ± 11.29, and 156.47 ± 26.62, respectively. There were no significant associations between selected socio-demographic/clinical variables and physical activity levels except in gender (χ 2 = 6.737; p = 0.034), fatigue severity except in side of affectation (χ 2 = 5.839; p = 0.054), and HRQL except in level of education (χ 2 = 23.497; p = 0.001) and side of affectation (χ 2 = 7.389; p = 0.007). There was a moderate and significant correlation (R = 0.426; p < 0.05) among PA, FS, and HRQL. Regression analysis revealed no significant associations with the socio-demographic/clinical variable except the side of affectation for HRQL, low (R = 0.223) level of prediction of socio-demographic/clinical variables for PA (F 8, 93 = 0.607; p > 0.05), and fair (R = 0.326) level of prediction for FS (F 8, 93 = 1.386; p > 0.05). Conclusion Moderate correlations among fatigue severity, physical activity, and health-related quality of life in stroke survivors suggested that enhancing one domain can benefit others, while the limited predictive ability of socio-demographic and clinical variables highlighted the need to consider cultural and psychological factors in post-stroke outcomes.